Implementasi Kebijakan Daerah Kabupaten Ponorogo dalam melakukan pentaaan kawasan Pedestarian Urip Sumoharjo - Luqman, Muhammad Aliba Nur; Hilman, Yusuf Adam (JURNAL DINAMIKA, 2024)
This research aims to analyze the implementation of the pedestrian area policy on Jalan Urip Sumoharjo, Ponorogo Regency, which aims to improve the quality of life through safe and comfortable public spaces for pedestrians. The research method uses a qualitative approach with in-depth interviews, field observations, and documentation studies. The results showed that there were obstacles in infrastructure, community involvement, and coordination between related parties, although there were successes in improving pedestrian comfort and safety as well as partial community support. Key success factors were community involvement in planning and monitoring and the government's active role in budget allocation. Research recommendations are to improve coordination between agencies, improve pedestrian infrastructure, and involve the community more intensively in monitoring and maintaining pedestrian areas.